Analisis Strategi Ekspansi Internasional Eiger - Prawinata, R. Teddy Adiyanto (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
The research delves into Eiger Adventure’s global expansion strategy, particularly its inaugural store in Interlaken, Switzerland. Eiger aims to introduce Indonesian identity and prove the quality of Indonesian products in the global market, while also showcasing Indonesian culture and beauty through its presence in Switzerland. The study analyzes various strategic concepts, methodologies, and specific strategies employed in the process, emphasizing the complexities and nuances involved in global marketing expansion. It discusses the significance of strategic adaptation, market research, and understanding consumer preferences in successfully expanding into international markets. The document also provides insights into Eiger’s meticulous research-based approach, specifically focusing on the careful implementation of dual adaptation as an integral part of their global expansion strategy. This approach not only demonstrates Eiger’s presence as a provider of outdoor gear in the global market but also showcases its sensitivity to the uniqueness and diversity of each market they target. The research methodology involves qualitative descriptive analysis utilizing secondary data sources from books, journals, articles, and other reliable references. In essence, the document offers a comprehensive analysis of Eiger Adventure’s global expansion strategy, shedding light on the strategic concepts, methodologies, and specific strategies employed in the process.